Factors influence on revisit: De Rhu Beach Resort / Muhammad Akmal Haikal Zainol Abidin - Zainol Abidin, Muhammad Akmal Haikal (2016)
Hospitality elements are closely related with the tourism industry, where resort industry was located. So, hospitality elements definitely will affect to the resort industry. This study represent on attempt to identify the hospitality attributes that lead to the revisit intention to the resort among the guest. In order to present the case study, researcher has attempted to synthesize findings from various research articles and distribution of questionnaire where samples of 120 resorts’ guest were all analyzed. With the use of SPSS statistical tools, the researcher then concluded that based on correlation analysis all of the recreation, accommodation, foods and beverages and service quality has significant relationship with the revisit intention, but through the regression analysis, somehow the foods and beverages attributes was not significant influence to the revisit intention